Simulation and Analysis of Wind Pressure Coefficient of Landslide-Type Long-Span Roof Structure. (24th February 2021) - Rong, Bin; Yin, Shuhao; Wang, Quankui; Yang, Yanhong; Qiu, Jian; Lin, Changsheng; Zhang, Ruoyu
Abstract : This article carries out a numerical simulation of a landslide-type long-span roof structure, Harbin Wanda Cultural Industry Complex. The maximum span of the landslide-type roof is 150 m and the minimum span is 90 m, with a minimum height of 40 m and a maximum height of 120 m, and the roof area is divided into three different parts. The large eddy simulation (LES) method is used to simulate and record the wind pressure coefficient of the roof. The distribution law and cause of the mean wind pressure coefficient of the roof are firstly analyzed, and the comparison with the existing wind tunnel test data proves the validity of the numerical simulation. Secondly, a qualitative analysis is made on the distribution of root mean square (RMS) fluctuating coefficients. Subsequently, the non-Gaussian characteristics of the roof are briefly discussed, and the peak factor distribution is calculated. Finally, based on the total wind pressure coefficient, a simple evaluation method for judging favorable and unfavorable wind direction angles is proposed, and only the shape of the roof and wind angle need to be known.